Pelatihan Pembuatan Kue Olahan Dari Singkong Untuk Menambah Nilai Ekonomis Di Desa Durian Kecamatan Peninjauan Kabupaten Ogan Komering Ulu - Novie Al Muhariah; Andri Irawan; Anis Feblin; Ali Akbar; Dahlia; Tati Herlina; Yetty Oktarina (Rumah Jurnal PT Citra Air Nusantara, 2026)
This community service activity aims to increase the economic value of cassava through training in making processed cassava-based cakes, specifically brownies, in Durian Village, Peninjauan District, Ogan Komering Ulu Regency. The main problem faced by the community in Durian Village is the lack of knowledge in processing cassava into cakes that have economic value. Through this training, participants consisting of housewives and PKK groups were provided with skills to process cassava into various cake products such as cassava brownies, cassava sponge cake, and cassava talam cake. The implementation method included stages of socialization, counseling, and direct demonstrations of making cassava-based brownies. The results of the activity showed an improvement in participants' skills and the emergence of plans to establish small businesses based on processed cassava products. This activity is expected to be an initial step in empowering household economies.